Australian social work academics' perceptions of their teaching roles within higher education. Issue 5 (29th July 2017) - Goldingay, Sophie; Lamaro Haintz, Greer; Ryan, Juliana; Hitch, Danielle; Macfarlane, Susie
ABSTRACT: The marketisation of higher education (HE) has created a number of tensions and ideological dilemmas that may influence how academics see their roles and teaching practices. This paper explores how academics in the discipline of social work (who were also in leadership roles) perceive their roles and identities and manage the tensions and dilemmas that arise for them as teachers in the current HE environment. Unless the tensions and dilemmas are articulated, it is not possible to understand and manage their impact on academics. This may lead to the loss of quality learning experiences for students and lower workplace satisfaction. This paper addresses the research question: were there ideological dilemmas experienced by social work academics in the current environment and if so, what subject positions did they adopt in response to these? A discursive psychology approach was used to answer this question. Data showed a range of ideological dilemmas represented by each of the different subject positions adopted. The paper concludes with questions for readers to consider, generating ideas for transferring understanding of these ideological dilemmas into positive action within the workplace.